2019
DOI: 10.7150/ijbs.29744
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of tRNA-Derived Small RNAs Reveals Novel Potential Therapeutic Targets of Traditional Chinese Medicine (Buyang-Huanwu-Decoction) on Intracerebral Hemorrhage

Abstract: Although Buyang-Huanwu-Decoction (BYHWD), a famous traditional Chinese medicine, has been utilized to promote the recovery of neurological function in intracerebral hemorrhage (ICH) for centuries, its therapeutic mechanisms remain unclear. tRNA-derived small RNA (tsRNA) is a novel class of short non-coding RNA, possessing potential regulating functions. In the current study, we explored the novel therapeutic targets of BYHWD by tsRNA-sequencing. Rats were randomly divided into three groups: sham, ICH, and BYHW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…The rats were weighed before and after the injury, and the percentage of weight change was calculated. The details of these tests were provided in our previous work (Xing et al, 2016;Li et al, 2019).…”
Section: Neurological Function Testingmentioning
confidence: 99%
“…The rats were weighed before and after the injury, and the percentage of weight change was calculated. The details of these tests were provided in our previous work (Xing et al, 2016;Li et al, 2019).…”
Section: Neurological Function Testingmentioning
confidence: 99%
“…Because tsRNAs have only recently been discovered, a database for tsRNA target prediction has not been available. Generally, the target predictions of tsRNArelated mRNAs have no unified algorithm, and the main principle of such predictions is based on miRNA-like methods (Li et al, 2019). Therefore, in the present study, we used two common miRNA algorithms to predict the targets of five CR pretreatment-related tsRNAs, and the roles each tsRNA FIGURE 7 | Target mRNAs regulated by four candidate tsRNAs enriched in macromolecular metabolic process and their verification via qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The modified neurological severity score (mNSS) was calculated according to previous methods (Li et al, 2019), and the detailed scoring rules are shown in Supplementary Table S2. The score is based on an evaluation of the neurological defects, according to aspects of movement, sensation, balance, etc.…”
Section: Modified Neurological Severity Scorementioning
confidence: 99%